2023
DOI: 10.1002/cctc.202300478
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Portfolio by a Novel Monomeric Oleate Hydratase from Pediococcus parvulus

Abstract: Oleate hydratases convert oleic acid into 10‐hydroxy stearic acid, a valuable fine chemical, useful in lubricant and surfactant formulations. They are of large interest due to their high expression rates and solubility, however, they differ drastically by their overall stability and pH‐ and temperature ranges. To expand their portfolio, another oleate hydratase named OhyPp (originating from Pediococcus parvulus) was characterized. It is a close relative of the well‐known oleate hydratase OhyRe from Rhodococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Additionally, the composition of the triglycerides might affect the yield due to the preferences of the lipase [42,43]. Linseed oil contains large amounts of C18:2 and C18:3, which are also substrates for OhyRe [17] and other OHs [18], and thus, could bind and might lead to side reactions, resulting in a lower yield, whereas in C. oleaginosus oil, the most abundant fatty acid after oleic acid is C16:0 (Table 1). Thus, this oil might be beneficial regarding the oleic acid content relative to other C18 species.…”
Section: A Cascade Reaction Using a Lipase And Ohyrementioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the composition of the triglycerides might affect the yield due to the preferences of the lipase [42,43]. Linseed oil contains large amounts of C18:2 and C18:3, which are also substrates for OhyRe [17] and other OHs [18], and thus, could bind and might lead to side reactions, resulting in a lower yield, whereas in C. oleaginosus oil, the most abundant fatty acid after oleic acid is C16:0 (Table 1). Thus, this oil might be beneficial regarding the oleic acid content relative to other C18 species.…”
Section: A Cascade Reaction Using a Lipase And Ohyrementioning
confidence: 99%
“…Surprisingly, the first pH optimum shifted towards a more basic environment compared to when 12-HSA was used as the substrate. Since oleic acid has a pk a of 5.02 [18], we investigated the effect on the pH and whether this might be the reason for the activity shift. We indeed observed that the pH was shifted when 12-HSA was present in the reaction buffer, but it could not explain the change in the optimum (Table S1), thus indicating that the type of substrate for secADH can influence the reaction optima.…”
Section: Adh-coupled Assay Reaction Parameter Optimizationmentioning
confidence: 99%
See 3 more Smart Citations